SOME THOUGHTS ON THE BOOK: ‘UNA VISIÓN COMPARADA E INTERNACIONAL DEL DERECHO COOPERATIVO Y DE LA ECONOMÍA SOCIAL Y SOLIDARIA. LIBER AMICORUM PROFESOR DANTE CRACOGNA’ [A COMPARATIVE AND INTERNATIONAL VIEW OF COOPERATIVE LAW AND THE SOCIAL AND SOLIDARITY EC - Cáceres, Daniel Hernández (International Journal of Cooperative Law, 2024)
This collective and comprehensive work, of 632 pages, coordinated by Professors Hagen Henrÿ of the University of Helsinki and Carlos Vargas Vasserot, Director of the CIDES Research Center of the University of Almeria, honoring Professor Dante Cracogna on his 80thbirthday, provides a comprehensive study of cooperative law and the social economy at the global level. A clear sign of the internationality and globality of this work is that it contains 30 chapters written by 32 authors from 23 universities from 3 different continents. Although it is mainly written in Spanish, it also has contributions in English and French.